National Development Plan (NDP): 2021 - 2015 - Federal Ministry of Finance, Budget and National Planning (Nigeria Federal Ministry of Finance, Budget and National Planning)
This plan was formulated against the backdrop of several subsisting development challenges in the country and the need to tackle them within the framework of medium - and - long term plans.
Volume 1
osc 25/04/23
Arch
Keywords: Development plan; Economic Development; Economic policy; Nigeria